Long-term flame-retardant soluble polyimide adhesive film for lithium battery and preparation method of long-term flame-retardant soluble polyimide adhesive film
By polymerizing a specific aromatic diamine and dianhydride in the lithium battery bonding film, a soluble polyimide bonding film with long-term flame retardant is solved, and the problem of flame retardant efficiency reduction in the migration of flame retardant in the prior art is solved, and the effect of long-term flame retardant and high mechanical properties for lithium batteries is achieved.
Patent Information
- Application Number
- CN202411832295.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The migration of flame retardant agents in existing lithium battery bonding membrane materials during long-term use leads to a decrease in flame retardant efficiency, which cannot meet the long-term flame retardant needs of lithium batteries.
The polymerization is carried out using aromatic diamines and dianhydrides containing indandiamine, fluorine diamine, phosphorus-containing diamine and ester-containing diamine to form a long-term flame-retardant soluble polyimide bonding film, and the flame retardant, mechanical and dielectric properties of the material are improved through specific preparation methods.
It realizes long-term flame retardant and low electrolyte swellability for lithium batteries, improves the mechanical and dielectric properties of the materials, and meets the high-performance needs of lithium battery materials.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to a long-term flame-retardant soluble polyimide adhesive film for lithium batteries and a preparation method thereof, belonging to the technical field of polymer materials. Background Art
[0002] As my country's environmental requirements continue to increase, the call for emerging energy to replace traditional energy is getting louder and louder, and new energy materials, led by lithium batteries, have attracted much attention. Adhesive film is one of the important components of lithium-ion battery pole pieces. It is a polymer compound that adheres the active material and conductive agent in the electrode sheet to the electrode current collector. It has the function of enhancing the contact between the active material, conductive agent and current collector and stabilizing the pole sheet structure. It is an additional material with high technical content in lithium-ion battery materials. Although the amount of adhesive film used in the electrode sheet is relatively small, the performance of the adhesive film directly affects the capacity, life and safety of the battery.
[0003] At present, the lithium battery adhesive film market is dominated by PVDF. However, due to the characteristics of this type of material being easily swollen by electrolytes, low safety, and poor mechanical properties, its widespread application is limited. As the most promising high-performance polymer in the 21st century, polyimide materials have become an important choice in the field of lithium battery materials due to their excellent properties such as high corrosion resistance, high heat resistance, and high energy density.
[0004] Chinese patent application CN 118620570A discloses a polyimide composite adhesive film composition, a covering film and a preparation method thereof, wherein the flame retardant properties of the polyimide material are improved by adding a blended flame retardant. However, such flame retardants may cause the flame retardant to migrate during long-term use, thereby reducing the flame retardant efficiency and failing to achieve a long-term flame retardant effect for lithium batteries. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a long-term flame-retardant soluble polyimide adhesive film for lithium batteries and a preparation method thereof. The polyimide adhesive film has the good properties of solvent solubility and long-term flame retardancy for lithium batteries, and also has the outstanding characteristics of low electrolyte swelling and high mechanical properties, and has good application prospects in the field of new energy adhesive films.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a long-term flame-retardant soluble polyimide adhesive film for lithium batteries, wherein the polyimide adhesive film is polymerized from aromatic diamines including indane diamine, fluorine-containing diamine, ester-containing diamine, phosphorus-containing diamine and aromatic dianhydride.
[0007] Furthermore, the indane diamine is 5(6)-1-(4-aminophenyl)-1,3,3-trimethylindane (PIDA).
[0008] Furthermore, the fluorinated diamine is at least one of the following structures:
[0009]
[0010] Furthermore, the phosphorus-containing diamine is at least one of the following structures:
[0011]
[0012] Furthermore, the ester-containing diamine is at least one of the following structures:
[0013]
[0014] Furthermore, the aromatic dianhydride is at least one of the following structures:
[0015]
[0016] The present invention also discloses a method for preparing a long-term flame-retardant soluble polyimide adhesive film for lithium batteries, and the preparation method is as follows:
[0017] S1: Under the protection of inert gas, indane diamine, fluorine-containing diamine, phosphorus-containing diamine, and ester-containing diamine are dissolved in a non-protonic polar solvent in a certain proportion;
[0018] S2: adding aromatic dianhydride in batches, adjusting the ratio of aromatic diamine to aromatic dianhydride, controlling the solid content of the system, and performing polycondensation reaction at a certain temperature to obtain a polyamic acid solution;
[0019] S3: adding a catalyst and a dehydrating agent to the polyamic acid solution to carry out a chemical imidization reaction, and after the reaction is completed, precipitating the product in a poor solvent, washing with water, and drying to obtain a polyimide solid;
[0020] S4: dissolving the polyimide solid in a non-protonic polar solvent, coating to form a film, and obtaining a polyimide adhesive film product after gradient heating and vacuum drying.
[0021] Further, in step S1, the molar ratio of the indane diamine, the fluorine-containing diamine, the phosphorus-containing diamine, and the ester-containing diamine is (0.25-0.35): (0.1-0.3) (0.1-0.3): (0.15-0.35);
[0022] In step S2, the molar ratio of the aromatic diamine to the aromatic dianhydride is (1.02-1.05):1; the solid content range is 10%-25%; the polycondensation reaction temperature is 10°C-40°C;
[0023] Furthermore, in step S3, the catalyst is one or more of pyridine, triethylamine, quinoline, and isoquinoline; the dehydrating agent is one or more of acetic anhydride, phthalic anhydride, and N,N-dicyclohexylcarbodiimide; and the poor solvent is one or more of deionized water, methanol, ethanol, and acetone.
[0024] Furthermore, in steps S1 and S4, the aprotic polar solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide;
[0025] In step S4, the specific operation steps of the gradient heating are as follows: after heating to 50°C, keep warm for 0.5-1h; then heat to 65°C and keep warm for 30-60min; continue to heat to 80°C and keep warm for 30-60min; finally heat to 100°C and keep warm for 60-90min; the temperature of the vacuum drying is 150°C and the time is 120-180min.
[0026] The beneficial effects of the present invention are:
[0027] The present invention introduces phosphorus-containing diamine into polyimide in an intrinsic flame retardant manner to permanently enhance its flame retardant properties. The aromatic diamine containing an ester group and the aromatic dianhydride containing a rigid structure improve the mechanical properties of the material, improve the electrolyte wettability and swelling resistance of the material in the electrolyte, and the indane diamine and the fluorine-containing diamine enhance the dielectric properties of the material while improving the solubility of the material.
[0028] The present invention obtains a polyimide adhesive film material with outstanding comprehensive performance through the synergistic combination of indane diamine, fluorine-containing diamine, phosphorus-containing diamine, ester-containing diamine and aromatic dianhydride, and has good application prospects in the field of lithium battery materials. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0031] Example 1
[0032] In N 2 Under protection, 0.7991 g (3 mmol) of PIDA, 0.985 g of m-BAPPO (2 mmol), 0.8006 g of TFMB (2.5 mmol) and 0.5706 g of APAB (2.5 mmol) were added to a 50 mL three-necked flask, and then N,N-dimethylformamide was added and stirred to dissolve.
[0033] The reaction temperature was set at 20° C., 3.1904 g BTDA (9.9 mmol) was added in three batches, the solid content of the system was maintained at 25%, and the reaction was continued with stirring for 10 h to obtain a polyamic acid solution.
[0034] Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and then heated and dried by air blowing to finally obtain a polyimide solid.
[0035] The dried polyimide solid was redissolved in N,N-dimethylformamide to prepare a polyimide solution with a solid content of 20%, and the solution was coated on a glass substrate. The glass substrate was heated to 50°C and kept for 45 minutes; heated to 65°C and kept for 45 minutes; then heated to 80°C and kept for 1 hour, and then heated to 100°C and kept for 1 hour, and finally vacuum dried at 150°C for 2 hours to obtain a polyimide adhesive film product.
[0036] Example 2
[0037] In N 2 Under protection, 0.9323 g PIDA (3.5 mmol), 0.7388 g m-BAPPO (1.5 mmol), 1.1890 g BTAB (3 mmol) and 0.6967 g ABHQ (2 mmol) were added into a 50 mL three-necked flask, and then N,N-dimethylformamide was added and stirred to dissolve.
[0038] The reaction temperature was set at 30°C, 2.7950 g BPDA (9.8 mmol) was added in three batches, the solid content of the system was maintained at 20%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution. Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and heated to dry by air to finally obtain a polyimide solid.
[0039] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept warm for 45 minutes; heated to 65°C and kept warm for 45 minutes; then heated to 80°C and kept warm for 1 hour, and then heated to 100°C and kept warm for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0040] Example 3
[0041] In N 2 Under protection, 0.6659 g PIDA (2.5 mmol), 0.304 g DAPOP (2 mmol), 0.9611 g FFDA (2.5 mmol) and 1.0451 g BAPT (3 mmol) were added into a 50 mL three-necked flask, and then N,N-dimethylacetamide was added and stirred to dissolve.
[0042] The reaction temperature was set at 20°C, 4.5375 g TAHQ (9.9 mmol) was added in three batches, the solid content of the system was maintained at 15%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution. Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and then heated and dried by forced air to finally obtain a polyimide solid.
[0043] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept for 45 minutes; heated to 65°C and kept for 45 minutes; then heated to 80°C and kept for 1 hour, and then heated to 100°C and kept for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0044] Example 4
[0045] In N 2 Under protection, 0.7991 g PIDA (3 mmol), 0.228 g DAPOP (1.5 mmol), 0.9607 g TFMB (3 mmol) and 0.6209 g BAPT (2.5 mmol) were added into a 50 mL three-necked flask, and then N,N-dimethylacetamide was added and stirred to dissolve.
[0046] The reaction temperature was set at 30°C, 3.3146 g 8CI (9.8 mmol) was added in three batches, the solid content of the system was maintained at 20%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution. Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and then heated and dried by air blowing to finally obtain a polyimide solid.
[0047] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept warm for 45 minutes; heated to 65°C and kept warm for 45 minutes; then heated to 80°C and kept warm for 1 hour, and then heated to 100°C and kept warm for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0048] Example 5
[0049] In N 2 Under protection, 0.7458 g PIDA (2.8 mmol), 0.726 g BAMP (3 mmol), 0.5021 g APAB (2.2 mmol) and 0.6685 g FA (2 mmol) were added into a 50 mL three-necked flask, followed by the addition of N-methylpyrrolidone and stirring to dissolve.
[0050] The reaction temperature was set at 30°C, 4.5375 g PHAP (9.9 mmol) was added in three batches, the solid content of the system was maintained at 20%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution. Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and heated to dry by air blowing to finally obtain a polyimide solid.
[0051] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept warm for 45 minutes; heated to 65°C and kept warm for 45 minutes; then heated to 80°C and kept warm for 1 hour, and then heated to 100°C and kept warm for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0052] Example 6
[0053] In N 2Under protection, 0.8524 g PIDA (3.2 mmol), 0.88 g BAPP (2.5 mmol), 0.4565 g APAB (2 mmol) and 0.9116 g BTAB (2.3 mmol) were added into a 50 mL three-necked flask, and then N,N-dimethylacetamide was added and stirred to dissolve.
[0054] The reaction temperature was set at 40°C, 5.2374 g BP-TME (9,8 mmol) was added in three batches, the solid content of the system was maintained at 25%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution. Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and heated to dry by air blowing to finally obtain a polyimide solid.
[0055] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept warm for 45 minutes; heated to 65°C and kept warm for 45 minutes; then heated to 80°C and kept warm for 1 hour, and then heated to 100°C and kept warm for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0056] Comparative Example 1
[0057] The polyimide adhesive film was prepared by the same method as in Example 1, except that m-BAPPO was replaced with an equal molar amount of APAB. The specific preparation process is as follows:
[0058] In N 2 Under protection, 0.7991 g PIDA (3 mmol), 0.8006 g TFMB (2.5 mmol) and 1.0271 g APAB (4.5 mmol) were added into a 50 mL three-necked flask, and then N,N-dimethylformamide was added and stirred to dissolve.
[0059] The reaction temperature was set at 20° C., 3.1904 g BTDA (9.9 mmol) was added in three batches, the solid content of the system was maintained at 25%, and the reaction was stirred for 10 hours to obtain a polyamic acid solution.
[0060] Pyridine and acetic anhydride were added to the polyimide solution, and the reaction was stirred for 16 hours. The reaction product was slowly poured into a large amount of deionized water to obtain a white precipitate. The white precipitate was washed with water, filtered, and then heated and dried by air blowing to finally obtain a polyimide solid.
[0061] The dried polyimide solid was redissolved in N, N-dimethylacetamide to prepare a polyimide solution with a solid content of 20%, and coated on a glass substrate. The glass substrate was heated to 50°C and kept warm for 45 minutes; heated to 65°C and kept warm for 45 minutes; then heated to 80°C and kept warm for 1 hour, and then heated to 100°C and kept warm for 1 hour, and finally vacuum dried at 150°C for 2 hours.
[0062] Comparative Examples 2-3
[0063] The polyimide adhesive film was prepared by the same method as in Example 1, except that m-BAPPO was replaced by PIDA and TFMB in equal molar amounts, and the specific formula is shown in Table 1.
[0064] Comparative Examples 4-6
[0065] The polyimide adhesive film was prepared by the same method as in Example 1, except that APAB was replaced by PIDA, m-BAPPO and TFMB in equal molar amounts, respectively. The specific formula is shown in Table 1:
[0066] Comparative Examples 7-9
[0067] The polyimide adhesive film was prepared by the same method as in Example 1, except that PIDA was replaced by APAB, m-BAPPO and TFMB in equal molar amounts. The specific formula is shown in Table 1:
[0068] Comparative Examples 10-12
[0069] The polyimide adhesive film was prepared by the same method as in Example 1, except that TFMB was replaced with PIDA, m-BAPPO and APAB in equal molar amounts. The specific formula is shown in Table 1:
[0070] Comparative Example 13
[0071] The polyimide adhesive film was prepared by the same method as in Example 1, except that the gradient heating method of the present invention was not used during the drying process. The specific heating process is as follows:
[0072] The glass substrate was heated to 50°C and kept for 45 min, then heated to 80°C and kept for 1 h, and then heated to 100°C and kept for 1 h, and finally vacuum dried at 150°C for 2 h.
[0073] The polyimide adhesive films obtained in the above examples and comparative examples were tested according to the following test methods. The test results are shown in Table 2. The specific test methods involved are:
[0074] Limiting Oxygen Index: Use an oxygen index analyzer to test the flame retardant properties of polyimide.
[0075] 5% thermal decomposition temperature: tested using a thermogravimetric analyzer.
[0076] Mechanical properties: The mechanical properties of the adhesive film were tested in accordance with GB / T 1040.3-2006.
[0077] Electrolyte swelling resistance test: 2g of polyimide micelles were immersed in 14g of a sealed lithium-sulfur electrolyte (1M LiTFSI in DME = 100Vol%) at 70°C for 168h. The immersed polyimide micelles were dried at 70°C for 10h, and the mass change rate of the dried polyimide micelles compared with the initial micelles was tested.
[0078] Adhesion test: Polyimide is coated on the surface of the conductive substrate and subjected to a cross-cutting adhesion test according to GB / T 9286-98. Grade 0 represents the best adhesion and grade 5 represents the worst adhesion.
[0079] Table 1 Comparative Examples 1-12 Formula composition of aromatic diamine monomers
[0080]
[0081] Note: In Table 1, monomer 1, monomer 2 and monomer 3 are aromatic diamines, and monomer 4 is an aromatic dianhydride; wherein, the molar percentages of monomer 1, monomer 2 and monomer 3 are: the molar percentage of each monomer in the aromatic diamine (the sum of the molar percentages of monomer 1, monomer 2 and monomer 3 is 100%); the molar percentage of monomer 4 is: the percentage of the molar amount of monomer 4 in the total molar amount of the aromatic diamine. )
[0082] Table 2 Performance test results of polyimide adhesive film
[0083]
[0084] By comparing the test results of Examples 1-6 and Comparative Examples 1-3, it can be seen that when the phosphorus-containing diamine is missing from the diamine monomer, the limiting oxygen index of the obtained product is significantly reduced;
[0085] By comparing the test results of Examples 1-6 and Comparative Examples 4-6, it can be seen that when the ester-containing diamine is missing from the diamine monomer, the electrolyte swelling resistance and adhesion of the obtained product are reduced;
[0086] By comparing the test results of Examples 1-6 and Comparative Examples 7-9, it can be seen that when the diamine monomer lacks indane diamine, the resulting product will gel during the reaction and lose fluidity;
[0087] By comparing the test results of Examples 1-6, Comparative Examples 4-6 and Comparative Examples 10-12, it can be seen that when the fluorine-containing diamine is missing from the diamine monomer, the bonding performance of the obtained product decreases; the ester-containing diamine and the fluorine-containing diamine have a synergistic effect in improving the bonding strength of the product;
[0088] By comparing the test results of Examples 1-6 and Comparative Example 13, it can be seen that when the preparation process does not follow the gradient temperature increase conditions specified in the present invention, the flame retardancy, mechanical and adhesive properties of the product will be reduced due to defects caused by rapid evaporation of the solvent.
[0089] In general, when the polyimide adhesive film prepared by the present invention lacks any one of the required indane diamine, fluorine-containing diamine, phosphorus-containing diamine and ester-containing diamine, the overall performance of the polymer is poor.
[0090] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A long-term flame-retardant soluble polyimide adhesive film for lithium batteries, characterized in that: The polyimide adhesive film is prepared by polymerizing aromatic diamines including indane diamine, fluorine-containing diamine, ester-containing diamine, phosphorus-containing diamine, and aromatic dianhydride.
2. A long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to claim 1, characterized in that: The indandiamine is 5(6)-1-(4-aminophenyl)-1,3,3-trimethylindan.
3. The long-term flame-retardant soluble polyimide adhesive film for lithium battery according to claim 1, characterized in that: The fluorinated diamine is at least one of the following structures:
4. The long-term flame-retardant soluble polyimide adhesive film for lithium battery according to claim 1, characterized in that: The phosphorus-containing diamine is at least one of the following structures:
5. The long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to claim 1, characterized in that: The ester-containing diamine is at least one of the following structures:
6. The long-term flame-retardant soluble polyimide adhesive film for lithium battery according to claim 1, characterized in that: The aromatic dianhydride is at least one of the following structures:
7. A method for preparing a long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to any one of claims 1 to 6, characterized in that: The preparation method is as follows: S1: Under the protection of inert gas, indane diamine, fluorine-containing diamine, phosphorus-containing diamine, and ester-containing diamine are dissolved in a non-protonic polar solvent in a certain proportion; S2: adding aromatic dianhydride in batches, adjusting the ratio of aromatic diamine to aromatic dianhydride, controlling the solid content of the system, and performing polycondensation reaction at a certain temperature to obtain a polyamic acid solution; S3: adding a catalyst and a dehydrating agent to the polyamic acid solution to carry out a chemical imidization reaction, and after the reaction is completed, precipitating the product in a poor solvent, washing with water, and drying to obtain a polyimide solid; S4: dissolving the polyimide solid in a non-protonic polar solvent, coating to form a film, and obtaining a polyimide adhesive film product after gradient heating and vacuum drying.
8. The method for preparing a long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to claim 7, characterized in that: In step S1, the molar ratio of the indane diamine, the fluorine-containing diamine, the phosphorus-containing diamine, and the ester-containing diamine is (0.25-0.35): (0.1-0.3) (0.1-0.3): (0.15-0.35); In step S2, the molar ratio of the aromatic diamine to the aromatic dianhydride is (1.02-1.05):1; the solid content range is 10%-25%; and the polycondensation reaction temperature is 10°C-40°C.
9. The method for preparing a long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to claim 7, characterized in that: In step S3, the catalyst is one or more of pyridine, triethylamine, quinoline, and isoquinoline; the dehydrating agent is one or more of acetic anhydride, phthalic anhydride, and N,N-dicyclohexylcarbodiimide; and the poor solvent is one or more of deionized water, methanol, ethanol, and acetone.
10. The method for preparing a long-term flame-retardant soluble polyimide adhesive film for lithium batteries according to claim 7, characterized in that: In steps S1 and S4, the aprotic polar solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; In step S4, the specific operation steps of the gradient heating are as follows: after heating to 50°C, keep warm for 0.5-1h; then heat to 65°C and keep warm for 30-60min; continue to heat to 80°C and keep warm for 30-60min; finally heat to 100°C and keep warm for 60-90min; the temperature of the vacuum drying is 150°C and the time is 120-180min.
Citation Information
Patent Citations
Polyimide composite binder composition, cover film and preparation method thereof
CN118620570A
Cited By
Adhesive for compounding aluminum-plastic film of lithium battery and preparation method of adhesive
CN122405222A
A lithium battery aluminum plastic film composite adhesive and a preparation method thereof
CN122405222B